MEME POLITIK SEBAGAI SARANA KRITIK SOSIAL DI MEDIA FACEBOOK (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The study was titled political memes as a means of social criticism on Facebook. The purpose of this research is to find out the form of political meme submission as a means of social criticism of the 100-day program of Jokowi-Ma'uf's period II government in political memes on Facebook media. Whether political communication on social media in the future can be an input for the improvement of the political system in the future or not. This research is specifically at the reading of signs of meme posts uploaded on Facebook media, especially on posts related to the 100-day policy of Jokowi-Ma'ruf government period II starting after the inauguration, namely on October 20, 2019, to January 28, 2020, which is then described descriptively using a qualitative approach. Primary data comes from direct observations of meme posts uploaded on Facebook media. The data was then dissected using Roland Barthes' mark reading theory. The results of this research form a representation of the ideology or myth that the policies that Jokowi took in some ways are full of doubts and considered his policies cause a lot of controversy among the public, as well as public trust displayed in political memes, showing the low public confidence, especially the netizens about the ability of the government to run the system as well as produce policies that welfare of the people. The implications in this research are expected to contribute to the government and society in interpreting and understanding political communication activities on social media and providing awareness to the public to be more critical and not easily fooled by symbols and negative issues.